Evaluating non-relational storage technology for HEP metadata and meta-data catalog; Journal of Physics: Conference Series; Vol. 762, iss. 1 : Advanced Computing and Analysis Techniques in Physics Research (ACAT2016) - Grigorjeva (Grigorieva) M. A. Mariya Aleksandrovna; Golosova M. V. Marina Vladimirovna; Gubin M. Yu. Maksim Yurjevich; Klimentov A. A. Aleksey Anatoljevich; Osipova V. V. Viktoriya Viktorovna; Ryabinkin E. A. Evgeny Aleksandrovich (2016, 2016)
Title screen